2016
DOI: 10.1097/dss.0000000000000755
|View full text |Cite
|
Sign up to set email alerts
|

Bimatoprost 0.03% for the Treatment of Eyebrow Hypotrichosis

Abstract: BACKGROUNDEyebrow loss may have substantial negative functional and social consequences.OBJECTIVEEvaluate the safety and efficacy of bimatoprost 0.03% in subjects with eyebrow hypotrichosis.METHODSThis multicenter, double-masked study randomized adult females or males with eyebrow hypotrichosis to receive bimatoprost 0.03% twice (BID) or once daily (QD) or vehicle BID for 7 months. Primary endpoint was overall eyebrow fullness at Month 7. Secondary endpoints included eyebrow fullness (mm2), darkness (intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 23 publications
(29 reference statements)
0
31
0
Order By: Relevance
“…Bimatoprost was approved by the Food and Drug Administration for the treatment of eyelash hypotrichosis in 2008 [ 9 ]. The medication is a prostamide F 2α analogue; it demonstrated the side effect of eyelash growth when utilized in the treatment of glaucoma and ocular hypertension [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bimatoprost was approved by the Food and Drug Administration for the treatment of eyelash hypotrichosis in 2008 [ 9 ]. The medication is a prostamide F 2α analogue; it demonstrated the side effect of eyelash growth when utilized in the treatment of glaucoma and ocular hypertension [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prompted by the excellent response of eyelash growth with use of bimatoprost 0.03% solution, a small number of investigators have utilized bimatoprost to treat eyebrow hypotrichosis (Table 3 ) [ 3 - 7 , 9 ]. The studies included both women and men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016, Carruthers et al performed a multicenter, randomized, double-blind study to compare the efficacy and safety of twice-daily topical bimatoprost 0.03% treatment, once-daily topical bimatoprost 0.03% treatment, and twice-daily vehicle treatment for 7 months for 357 patients with eyebrow hypotrichosis. 61 Assessment was performed using the GEyA scale and Digital Monitoring System Analysis, and subject satisfaction was determined using the nine-item Eyebrow Satisfaction Scale. The results indicated that bimatoprost 0.03% twice daily and once daily showed favorable results starting at month 2, with marked improvement at month 7, with no serious side effects and no differences in eyebrow improvements for the two drug groups regarding the treatment of eyebrow hypotrichosis.…”
Section: Bimatoprost For the Treatment Of Eyebrow Hypotrichosismentioning
confidence: 99%